1967
DOI: 10.1039/j39670001822
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic polyfluoro-compounds. Part X. Nucleophilic substitution in tetrafluoropyrimidine

Abstract: Tetrafluoropyrimidine, prepared in high yield by reaction of tetrachloropyrimidine with anhydrous potassium fluoride at elevated temperatures, is highly susceptible to attack by nucleophiles; the ease of displacement of ring fluorines decreases in the order 4-and 6-> 2-5 5-. Through use of appropriate nucleophilic reagents the following fluoro-pyrimidines have been prepared : 4-X*C4F3N2 (X = OH), 4-YC4F3N2, and4,6-Y,*C4F,N2 (Y = NH,, OMe, NHPh. NHMe. or NMe,). and 2,4,6-Z,*C4FN, (2 = OMe). The structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Reaction of 1 with ammonia results in two isomeric products, as observed by 19 F NMR analysis of the reaction mixture which displayed two distinctive peaks (−48.18 and −69.47 ppm) for the 4-substituted isomer and one peak (−65.44 ppm) for the 2-isomer in a 9 : 1 ratio, the chemical shifts being consistent with previous studies [ 18 ]. Similarly, reaction of 1 with ethylamine gives two isomers in an 8 : 1 ratio by 19 F NMR as shown by the appearance of two fluorine signals (−47.48 and −70.83 ppm) and one signal (−63.59 ppm) corresponding to the 4- and 2-amino isomers respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Reaction of 1 with ammonia results in two isomeric products, as observed by 19 F NMR analysis of the reaction mixture which displayed two distinctive peaks (−48.18 and −69.47 ppm) for the 4-substituted isomer and one peak (−65.44 ppm) for the 2-isomer in a 9 : 1 ratio, the chemical shifts being consistent with previous studies [ 18 ]. Similarly, reaction of 1 with ethylamine gives two isomers in an 8 : 1 ratio by 19 F NMR as shown by the appearance of two fluorine signals (−47.48 and −70.83 ppm) and one signal (−63.59 ppm) corresponding to the 4- and 2-amino isomers respectively.…”
Section: Resultssupporting
confidence: 91%
“…Whilst 1 is commercially available and has been known for some time, only a limited number of reactions have been reported (e.g. with ammonia to give the 4-amino derivative [ 18 ]) despite the fact that 1 is used widely in the fibre reactive dye industry [ 19 ]. However, a systematic study of the reactivity of this potentially valuable scaffold with other nitrogen nucleophiles has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…meta ( 4 J) 19 F- 19 F coupling constants that are considerably smaller than those for ortho and para coupling (or even absent) have been commonly reported for heavily fluorinated aryl systems. [39][40][41][42][43] It has been suggested that this is because π-conjugation contributes significantly to 19 F- 19 F coupling in aromatics. 39,43 We propose that this restriction of rotation is due to intramolecular π-π interactions.…”
Section: Design Synthesis and Characterisationmentioning
confidence: 99%
“…Tetrachloropyrimidine may be converted into 5-chlorotrifluoropyrimidine by reaction with silver fluoride [578] or into the perfluoro-compound by reaction with anhydrous caesium or potassium fluoride, preferably at elevated temperatures (410-480°) in an autoclave [214,569,583] . When the perchloro-compound is reacted with hydrofluoric acid in a nickel autoclave at 130° for 10 h, it yields a mixture of 5-chlorotrifluoropyrimidine (6%), a dichlorodifluoropyrimidine (39%), which is probably the 5,6-dichloro-2,4difluoro-compound, and a trichlorofluoropyrimidine (47%), which is probably trichloro-4-fluoropyrimidine [584] .…”
Section: Cl'q'n'ccicci'mentioning
confidence: 99%
“…2,4,6-Trichloropyrimidine is converted into 2,4,6-trifluoropyrimidine on treatment with potassium [583,[585][586][587] or silver fluoride [531,578,588]. Lower fluorinated products may be formed also, depending on the reaction conditions.…”
Section: Cl'q'n'ccicci'mentioning
confidence: 99%